Image‐scoring system for umbilical and uterine artery pulsed‐wave Doppler ultrasound measurement. (5th February 2019) - Molloholli, M.; Napolitano, R.; Ohuma, E. O.; Ash, S.; Wanyonyi, S. Z.; Cavallaro, A.; Giudicepietro, A.; Barros, F.; Carvalho, M.; Norris, S.; Min, A. M.; Zainab, G.; et al.
ABSTRACT: Objectives: To develop an objective image‐scoring system for pulsed‐wave Doppler measurement of maternal uterine and fetal umbilical arteries, and evaluate how this compares with subjective assessment. Methods: As an extension to the INTERGROWTH‐21 st Project, we developed a scoring system based on six predefined criteria for uterine and umbilical artery pulsed‐wave Doppler measurements. Objective evaluation using the scoring system was compared with subjective assessment which consisted of classifying an image as simply acceptable or unacceptable. Based on sample size estimation, a total of 120 umbilical and uterine artery Doppler images were selected randomly from the INTERGROWTH‐21 st image database. Two independent reviewers evaluated all images in a blinded fashion, both subjectively and using the six‐point scoring system. Percentage agreement and kappa statistic were compared between the two methods. Results: The overall agreement between reviewers was higher for objective assessment using the scoring system (agreement, 85%; adjusted kappa, 0.70) than for subjective assessment (agreement, 70%; adjusted kappa, 0.47). For the six components of the scoring system, the level of agreement (adjusted kappa) was 0.97 for anatomical site, 0.88 for sweep speed, 0.77 for magnification, 0.68 for velocity scale, 0.68 for image clarity and 0.65 for angle of insonation. Conclusion: In quality assessment of umbilical and uterine artery pulsed‐wave Doppler measurements, our proposed objective six‐point image‐scoring system is associated with greater reproducibility than is subjective assessment. We recommend this as the preferred method for quality control, auditing and teaching. Copyright © 2018 ISUOG. Published by John Wiley & Sons Ltd.